Solid-state devices and applications. - Lewis, Rhys (Newnes-Butterworths, 1971)
Solid-State Devices and Applications is an introduction to the solid-state theory and its devices and applications. The book also presents a summary of all major solid-state devices available, their theory, manufacture, and main applications. The text is divided into three sections. The first part deals with the semiconductor theory and discusses the fundamentals of semiconductors; the kinds of diodes and techniques in their manufacture; the types and modes of operation of bipolar transistors; and the basic principles of unipolar transistors and their difference with bipolar transistors. The s.